Determination of Soil Moisture Content using Laboratory Experimental and Field Electrical Resistivity Values - Hazreek Z.A.M.; Rosli S.; Fauziah A.; Wijeyesekera D.C.; Ashraf M.I.M.; Faizal T.B.M.; Kamarudin A.F.; Rais Y.; Md Dan M.F.; Azhar A.T.S.; Hafiz Z.M. (Institute of Physics Publishing, 2023)
Correlation methods; Drilling platforms; Electric conductivity; Electric resistance; Laboratories; Moisture determination; Particle size; Particle size analysis; Soil moisture; Soil testing; Characterization tests; Civil engineering structures; Coefficient of determination; Conventional approach; Drilling techniques; Geotechnical properties; Site investigations; Statistical correlation; Soil surveys